Ice Shelf/Ocean interactions at the front of Hells Gate Ice Shelf (Terra Nova Bay, Antarctica) - Tison, Jean-Louis; Barbante, Carlo; Bondesan, A.; Lorrain, Reginald; Capra, A. (1997)
info:eu-repo/semantics/published